Plasma polymers as targets for laser-driven proton-boron fusion - Tosca, Marco; Molloy, Daniel; McNamee, Aaron; Pleskunov, Pavel; Protsak, Mariia; Biliak, Kateryna; Nikitin, Daniil; Kousal, Jaroslav; Krtouš, Zdeněk; Hanyková, Lenka; Hanuš, Jan; Biederman, Hynek; et al. (Frontiers in Physics, 2023)
This is a provisional file, not the final typeset article Laser-driven proton-boron (pB) fusion has been gaining significant interest for energetic alpha particles production because of its neutron-less nature. This approach requires the use of B-and H-rich materials as targets, and common practice is the use of BN and conventional polymers. In this work, we chose plasma-assisted vapour phase deposition to prepare films of oligoethylenes (plasma polymers) on Boron Nitride BN substrates as an advanced alternative. The r.f. power delivered to the plasma was varied between 0 and 50 W to produce coatings with different crosslink density and hydrogen content, while maintaining the constant thickness of 1 μm. The chemical composition, including the hydrogen concentration, was investigated using XPS and RBS/ERDA, whereas the surface topography was analyzed using SEM and AFM. We triggered the pB nuclear fusion reaction focusing laser pulses from two different systems (i.e. the TARANIS multi-TW laser at the Queen's University Belfast (UK) and the PERLA B 10-GW laser system at the HiLASE center in Prague (Czech Republic)) directly onto these targets. We achieved a yield up to 10 8 and 10 4 alpha particles/sr using the TARANIS and PERLA B lasers, respectively. Radiative-hydrodynamic and particle-in-cell PIC simulations were performed to understand the laser-target interaction and retrieve the energy spectra of the protons. The nuclear collisional algorithm implemented in the WarpX PIC code was used to identify the region where pB fusion occurs. Taken together, the results suggest a complex relationship between the hydrogen content, target morphology, and structure of the plasma polymer, which play a crucial role in laser absorption, target expansion, proton acceleration and ultimately nuclear fusion reactions in the plasma.